Inner Retinal Dysfunction in the Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay - Borruat, François-Xavier; Holder, Graham E.; Bremner, Fion (Frontiers in Neurology, 2017)
The autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is associated with structural retinal abnormalities either directly visible on funduscopy or revealed by optical coherence tomography (OCT). Most patients with ARSACS have a whitish peripapillary appearance corresponding to a thickening of the peripapillary retinal nerve fiber layer. OCT has also shown an absence of the physiological foveal depression. Abnormal electroretinography (ERG) has previously been reported in only two cases, without further details. This report describes a patient with ARSACS in whom careful full-field ERG revealed dysfunction of the retinal On- bipolar cells with sparing of photoreceptor function. This is the first report of inner retinal dysfunction in ARSACS.